2014
DOI: 10.1159/000368176
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>BCR-ABL1</i></b><sup><i>+</i></sup> Acute Myeloid Leukemia: Clonal Selection of a <b><i>BCR-ABL1</i></b><sup><i>-</i></sup> Subclone as a Cause of Refractory Disease with Nilotinib Treatment

Abstract: The presence of a Philadelphia chromosome with a corresponding BCR-ABL1 rearrangement is the hallmark of chronic myeloid leukemia, but is considered a very rare event in de novo acute myeloid leukemia (AML). Here, we report the first case in which a dominant Philadelphia chromosome-positive subclone was detected upon relapse in a formerly Philadelphia chromosome-negative MLL-AF6+ AML. Due to refractory disease under salvage chemotherapy, the patient was started on nilotinib treatment. As a result, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…One patient achieved a CCyR, but died of a brain abscess, two patients had a transient response [73,76], and two patients had no response [66,75]. Interestingly, in three patients, the TKI treatment led to an eradication of the Ph-positive clone despite an overall refractory disease [65,74,77]. This clearly shows the clonal diversity of BCR-ABL+ AML in contrast to chronic phase CML, which is strictly addicted to BCR-ABL.…”
Section: Treatment Of Bcr-abl+ Amlmentioning
confidence: 88%
See 1 more Smart Citation
“…One patient achieved a CCyR, but died of a brain abscess, two patients had a transient response [73,76], and two patients had no response [66,75]. Interestingly, in three patients, the TKI treatment led to an eradication of the Ph-positive clone despite an overall refractory disease [65,74,77]. This clearly shows the clonal diversity of BCR-ABL+ AML in contrast to chronic phase CML, which is strictly addicted to BCR-ABL.…”
Section: Treatment Of Bcr-abl+ Amlmentioning
confidence: 88%
“…In 14 published cases, BCR-ABL was acquired upon AML relapse [11,55,[71][72][73][74][75][76][77]. In 7 of these 14 patients, the morphologic classification was given.…”
Section: ) Bcr-abl At Aml Relapsementioning
confidence: 99%
“…The appearance of BCR/ABL1 in AML has been described in combination with different class II aberrations such as CBFβ/MYH11, RUNX1/RUNX1T1, PML/RARa, and NPM1. Neuendorff et al [ 17 ] showed a case of BCR/ABL1 + MLL/AF6 + AML without NPM1 aberrations. MLL rearrangements were mostly considered as class II aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Aberration ist damit der diagnostische Marker schlechthin. Sie ist ebenfalls in einem Teil der akuten lymphatischen Leukämien (ALL) des Erwachsenen-und Kindesalters nachweisbar sowie in einem geringen Anteil der akuten myeloischen Leukämien (AML [3][4][5]). …”
Section: Hintergrundunclassified